COVID-19 and resilience innovations in food supply chains - Reardon, Thomas; Swinnen, Johan (International Food Policy Research Institute, 2020)
The COVID-19 pandemic has triggered intense discussions about the vulnerability of the world’s food systems and food supply chains (FSCs) and about the roles of different types of supply chains, such as local vs. global, in providing food security. We know that the spread of the novel coronavirus and government- imposed lockdowns and other restrictions have had a range of impacts on FSCs, and triggered a variety of creative innovations to keep supply chains running. To guide government policy responses going forward, and to facilitate a shift to more resilient FSCs in the long run, we need to understand several things: the role of various types of supply chains in food security; how resilient they have — or have not — been to the pandemic’s impacts; and what innovations are now emerging to improve their resilience.